Pengelolaan Sampah Berbasis Masyarakat di Kelurahan Bumi Waras - Adinda Sekar Tanjung; Alivia Salsabila Mute; Husna Tiara Putri (Universitas Batanghari Jambi, 2022)
The increasing number of residents and various community activities will be directly proportional to the volume of generation and composition of the waste produced. Waste management is a major problem faced by almost all regions in Indonesia, including Bandar Lampung City. Bumi Waras Village is one of the areas where waste management is still low. In dealing with waste problems, it can be done through community involvement, therefore this study aims to identify the form of community willingness to participate in waste management. This study uses quantitative methods with descriptive statistical analysis. The results of this study indicate that the community is willing to carry out waste management up to the collection stage with the assistance of adequate infrastructure. However, the community's willingness has not yet reached the level of waste processing at the source level.